ANTIOXIDANT AND ANTI-INFLAMMATORY PROPERTIES OF PTEROSPERMUM RUBIGINOSUM HEYNE EX WIGHT AND ARN AND PTEROSPERMUM RETICULATUM WIGHT AND ARN (STERCULIACEAE): AN IN VITRO COMPARATIVE STUDY - JACOB, JENSON; K, SREEJITH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Plants from the family Sterculiaceae are used as folk medicine for treating various diseases in India. This study aims to determine the antioxidant and anti-inflammatory properties of Pterospermum rubiginosum and Pterospermum reticulatum of the family Sterculiaceae. The barks of P. rubiginosum and P. reticulatum are used in traditional medicine especially in the treatment of wounds, sprains, bone fracture, etc. This study, we compare the antioxidant and anti-inflammatory potentials of the stem bark of these two plants. Methods: The free radical scavenging assays such as 2,2–diphenyl,1–picrylhydrazyl (DPPH), 2,2’–azino-bis(3-ethylbenzothiozoline-6-sulfonic acid) (ABTS), hydroxyl radical, nitric oxide radical, phosphormolybdenum assay, and reducing power assay are used for the measurement of antioxidant potentials. The in vitro anti-inflammatory activities of the extracts are evaluated by means of lipoxygenase (LOX) and protease inhibition. Results: Both P. rubiginosum and P. reticulatum scavenge DPPH (70.10% and 91.02%), ABTS (94.48 and 98.19%), hydroxy (76.02 and 87.67%), and nitric oxide (87.02 and 80.84%) radicals. Phosphomolybdenum assay and reducing power assay, used for the measurement of antioxidant potentials also showed good results. Regarding the anti-inflammatory potential, the methanolic extract of the plants shows anti-protease activity (51.29 and 64.93%) and anti-LOX activity (56%) while P. rubiginosum does not exhibit anti-LOX activity. Conclusion: The above results demonstrate that the plants P. rubiginosum and P. reticulatum are rich source of antioxidant and anti-inflammatory compounds and it is the first report on theantioxidant and anti-inflammatory properties of the barks of these plants.